Hubungan Faktor Sosio Ekonomi Dan Usia Kehamilan Dengan Kejadian Kekurangan Energi Kronis Pada Ibu Hamil Di Puskesmas Prambontergayang Kabupaten Tuban - Fauziah Rizki Andini (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
ABSTRACTBackground: Chronic Energy Deficiency can occur in women in reproductive age (WUS) and pregnant woman who have Mid Upper Arm Circumference (MUFA) <23.5 cm. In 2019 the number of occurrences of CED for pregnant women in Prambontergayang Public Health Center was exceeded the target of Tuban Regency by 10.8%. Events of CED can occur due to low levels of education, low knowledge of nutrition, low family income, maternal age <20 years or> 35 years, high maternal parity, and too close the pregnancy distance. Purpose: to analyze factors related to the incidence of CED in pregnant women in the Prambontergayang Health Center in 2019.Method: this study was an observational analytic study with a cross sectional design. The sample of the study was pregnant women in Prambontergayang Public Health Center, which amounted to 179 pregnant women by using simple random sampling. The variables used are age, education, occupation, income, and age of pregnancy. Data analysis was performed using the Chi Square test and Pearson's Test.Results: The results showed that the prevalence of pregnant women who experienced CED was 20.1% and the value of p on the variables of age (p<0.001), education (p=0.013), occupation (p=0.008), and income (p<0.001) had significance <0.05 which meant there was a relationship with the CED events. In the gestational age variable, p> 0.05, which means there was no relationship with the CED.Conclusion: the incidence of CED is related to the condition of pregnant women aged <20 years and> 35 years, low education, not working and low income. But there is no relationship between maternal gestational age with the incidence of CED. The advice that can be given is that the village government invites pregnant women and their families to actively participate in managing the productive economy and the Public Health Center provides information on nutritious foods so as to increase the knowledge of pregnant women.ABSTRAKLatar Belakang : Kekurangan Energi Kronis dapat terjadi padaiwanita usia subur (WUS) daniibu hamil yangimemiliki Lingkar Lengan Atasi(LiLA) <23,5 cm. Pada tahun 2019 jumlah kejadianiKEK ibu hamil di Puskesmas Prambontergayang melebihi target dari Kabupaten Tuban yaitu 10,8%.Tujuan : untuk mengetahui faktor yang mempengaruhi kejadian KEK pada ibu hamil di Puskesmas Prambontergayang Tahun 2019.Metode : Jenis penelitian yang digunakan adalah analitik dengan menggunakan pendekatan cross sectional. Sampel dari penelitian yaitu ibu hamil di Wilayah Kerja Puskesmas Prambontergayang yang berjumlah 179 ibu hamil yang dihitung dengan menggunakan teknik simple random sampling. Hasil : Hasil dari penelitian ini menunjukkkan bahwasanya usia, pendidikan, penghasilan dan pekerjaan memiliki hubungan dengan kejadian KEK dengan nilai sig (ρ value) kurang dari 0,05.Kesimpulan : adanya hubungan antara usia, pendidikan, pekerjaan, dan penghasilan pada KEKIdan tidakiadaihubungan antarai usia kehamilan denganiKEK. Saran bagi Puskesmas Prambontergayang adalah perlu mengadakan penyuluhan yang lebih intensif kepada ibu hamil mengenai penyebab dan dampak KEK bagi kehamilan. Sedangkan untuk peneliti selanjutnya bisa melakukan penelitian dengan jenis penelitiain yang berbeda ataupun variabel yang belum digunakan. Kata Kunci : KEK, ibu hamil, pendidikan, pekerjaan, usia ABSTRACTBackground : Chronic Energy Deficiency can occur in women of childbearing age (WUS) and pregnant women who have an Upper Arm Circumference (LiLA) <23.5 cm. In 2019 the number of KEK incidents of pregnant women in the Prambontergkesmas Health Center was exceeded the target of the Tuban District of 10.8%. Purpose : Theipurpose of this study was toidetermine theifactors that influence the incidenceiof KEK in pregnantiwomeniin Puskesmas Prambontergayang in 2019. Method : The type of research is analytic using cross sectional approach. The sample of the study was pregnant women in the Prambontergayang Health Center, totaling 179 pregnant women, which were calculated using simple random sampling technique.Result : The results of this study show that age, education, income and employment have a relationship with the KEK event with a sig (ρ value) of less than 0.05. Conclusion : The conclusioniof the studyiis the relationshipibetweeniage, education, occupation, andiincome in KEK and thereiis no relationshipibetween gestational ageiwith KEK. Suggestions for Prambontergayang Health Center are the need for more intensive counseling for pregnant women regarding the causes and effects of KEK for pregnancy. Whereas the next researcher can conduct research with different types of research or variables that have not been used. Keywords : KEK, pregnant woman, education, work, age